2013
DOI: 10.1089/jir.2012.0134
|View full text |Cite
|
Sign up to set email alerts
|

Proadrenomedullin and Serum Amyloid A as a Predictor of Subclinical Chorioamnionitis in Preterm Premature Rupture of Membranes

Abstract: Preterm premature rupture of membranes (PPROM) is defined as a spontaneous membrane rupture that occurs before the onset of labor and 37 weeks gestation. Subclinical intrauterine infection has been suggested as a very important etiological factor in the pathogenesis and subsequent morbidity related with PPROM. This study was performed to assess the levels of maternal proadrenomedullin (pro-ADM) and serum amyloid A (AA) in PPROM and its association with fetomaternal infectious morbidity. A total of 63 pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…In the literature, there were many reports that support the importance of CRP levels in chorioamnionitis patients (11,19,25,26). However, we did not find any difference in the CRP levels and WBC counts between chorioamnionitis (+) and (−) cases in PPROM patients.…”
Section: Chorioamnionitis Chorioamnionitis (+)contrasting
confidence: 79%
“…In the literature, there were many reports that support the importance of CRP levels in chorioamnionitis patients (11,19,25,26). However, we did not find any difference in the CRP levels and WBC counts between chorioamnionitis (+) and (−) cases in PPROM patients.…”
Section: Chorioamnionitis Chorioamnionitis (+)contrasting
confidence: 79%
“…This receptor has also been identified as being responsible for other activities such as neutrophil IL-8 release or intracellular calcium mobilization (8) . In a previous study, serum proadrenomedullin and SAA levels were reported to be elevated in patients with PPROM and PPROM having subclinical chorioamnionitis (9) .…”
Section: Introductionmentioning
confidence: 85%
“…Few studies investigated association between preterm premature rupture of membranes and serum amyloid A and compare it with other inflammatory markers (9) .…”
Section: Discussionmentioning
confidence: 99%
“…It is easy to predict the disease of infants born to mothers who had clinical findings of suspected or overt chorioamnionitis and any other signs of systemic infection, but neonatal sepsis may develop without any kind of maternal infection exist. Subclinical intrauterine infection has been implicated as a major etiological factor in the pathogenesis and subsequent morbidity associated with EOS developed due to preterm membrane rupture, but EOS can also be developed in infants born to mothers who had no risk factor of infection [8].…”
Section: Introductionmentioning
confidence: 99%